A highly active bifunctional solid acid for di(1-naphthyl)methane hydroconversion. (15th May 2018) - Teng, Qing-Qing; Wei, Xian-Yong; Sun, Yi-Bing; Wang, Sheng-Kang; Lv, Jing-Hui; Li, Zhan-Ku; Liu, Zhong-Qiu; Zong, Zhi-Min
Highlights: Hydrocraking and hydrogenation are very important reactions for coal conversion. Catalyst I specifically catalyzes DNM hydrocracking to naphthalene and 1-MN. Bifunctional solid acid catalyst II facilitates hydrogenation and hydrocracking. Catalyst V is the most effective for converting DNM to decalin and 1-MD. Abstract: Catalysts trifloromethanesulfonic acid (TFMSA)/treated attapulgite powder (TAP), Ni/TAP, and Ni-TFMSA/TAP with different Ni and TFMSA loadings were prepared. The typical catalysts were characterized with multiple instruments and used for catalyzing hydroconversion of di(1-naphthyl)methane (DNM), which was used as a coal-related model compound. The suitable loadings of Ni and TFMSA in Ni-TFMSA/TAP were determined to be 28.6% of Ni and 33% of TFMSA. Under optimal reaction conditions of 5 MPa of initial hydrogen pressure, 240 °C, and 4 h over Ni-TFMSA/TAP, DNM was completely converted, producing decalin and 1-methyldecalin as the main products. The result suggests that Ni-TFMSA/TAP is highly active for both cleaving the Car -Calk bond in DNM and hydrogenating the resulting naphthalene and 1-methylnaphthalene under mild conditions. Based on the identification of reaction products, the catalytic mechanism for DNM hydroconversion was discussed.